2017
DOI: 10.1021/jacs.7b10768
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-Stabilized Metal Nanoparticles as Efficient Catalysts for Reversible Dehydrogenation/Hydrogenation of N-Heterocycles

Abstract: Nanoparticles (Pd, Pt, Rh) stabilized by G4OH PAMAM dendrimers and supported in SBA-15 (MNPs/SBA-15 with M = Pd, Pt, Rh) were efficiently used as catalysts in the acceptorless dehydrogenation of tetrahydroquinoline/indoline derivatives in toluene (release of H) at 130 °C. These catalysts are air stable, very active, robust, and recyclable during the process. The reverse hydrogenation reaction of quinoline derivatives (H storage) was also optimized and successfully performed in the presence of the same catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(97 citation statements)
references
References 74 publications
1
96
0
Order By: Relevance
“…The acceptorless dehydrogenation of N‐heterocycles is an important reaction in organic synthesis, which also has potential in the storage of hydrogen . This reaction is usually carried out under thermal conditions, and recently shown possible to be catalyzed under visible light . The mechanism study revealed the multistep nature of the dehydrogenation process (Supporting Information, Figures S91, S92), which is suitable for the systematic study of MOFs with variable distance profiles.…”
Section: Figurementioning
confidence: 99%
“…The acceptorless dehydrogenation of N‐heterocycles is an important reaction in organic synthesis, which also has potential in the storage of hydrogen . This reaction is usually carried out under thermal conditions, and recently shown possible to be catalyzed under visible light . The mechanism study revealed the multistep nature of the dehydrogenation process (Supporting Information, Figures S91, S92), which is suitable for the systematic study of MOFs with variable distance profiles.…”
Section: Figurementioning
confidence: 99%
“…Previously, the benchmark two‐step highly endothermic AD‐reactions of tetrahydroquinolines (THQs) have been carried out with metal‐based homogeneous catalysts which are rarely recyclable and usually air‐sensitive, with heterogeneous noble‐metal NP based catalysts under unavoidable harsh conditions (temperature >135 °C, reaction time >24 h) and requiring additional oxidizers, bases, and hydrogen‐acceptors and also with few photocatalysts which are complicated to synthesize, requiring high furnace temperatures (ca. 1250 °C) under toxic ammonia flow, have narrow light absorption profile and take long reaction times using high catalyst amounts . Impressively, Pt‐Au‐based NCat demonstrated very clean AD reaction (yield >99 %) within short reaction time (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid organic hydrogen carriers (LOHCs) have been indeed proposed asc onvenient ands afe solutions for hydrogen storage. [6] Only very few homogeneous catalytic systemsc an both hydrogenate/dehydrogenate Nheterocycles. Heterogeneousc atalytic systems can in general be recovered and reused, but they require rather high temperatures compared to homogeneous catalysts.…”
mentioning
confidence: 99%
“…This result prompted us to investigate the catalytic performance of these complexes in the hydrogenation/dehydrogenation of N-heterocycles. 80 8Cw as selected as the temperature to further investigate the catalyst loading (Table 1, entries [6][7][8][9]. Several experimentalp arameters were screened and optimized.…”
mentioning
confidence: 99%
See 1 more Smart Citation